2021
DOI: 10.1111/aas.13998
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of prolonged intensive care and rehabilitation at a specialized multidisciplinary center in Sweden

Abstract: Background: Specialized clinics may improve the outcome for patients with prolonged intensive care stays. Admission may depend on diagnosis, need of respiratory support and more. We report the results from a Swedish specialized center with a multidisciplinary team approach to continued intensive care and simultaneous rehabilitation regardless of patients' primary diagnosis or ventilator need.Methods: All patients admitted and discharged from 2015 to 2018 were included.Demographics, diagnoses, ventilatory suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Patient acceptance of treatment was high and in only three cases could the therapy not be applied as a OWV could not be used. Mortality was low in line with previous research data from the center, 20 and causes of deaths were not considered related to HFT‐T‐OWV treatment. The one incident of pneumothorax in a patient with repeated pneumothoraxes was deemed unlikely to be related to the HFT‐T‐OWV treatment, a conclusion supported by the benchtop experiments where maximum pressures were <2 cmH 2 O using the OPT 970 adapter.…”
Section: Discussionsupporting
confidence: 76%
“…Patient acceptance of treatment was high and in only three cases could the therapy not be applied as a OWV could not be used. Mortality was low in line with previous research data from the center, 20 and causes of deaths were not considered related to HFT‐T‐OWV treatment. The one incident of pneumothorax in a patient with repeated pneumothoraxes was deemed unlikely to be related to the HFT‐T‐OWV treatment, a conclusion supported by the benchtop experiments where maximum pressures were <2 cmH 2 O using the OPT 970 adapter.…”
Section: Discussionsupporting
confidence: 76%
“…12,13 Löfroth and colleagues report on the outcome of ICU survivors who were transferred from Karolinska university clinic to their Remeo ICU rehabilitation unit in Stockholm, Sweden. 14 They showed that transfer from an ICU environment to a specialised ICU rehabilitation centre is safe (in clinic mortality 3%) and results in successful weaning from the ventilator in most patients, a very high decannulation rate of tracheostomised patients, and a negligible ICU readmission rate. These results are remarkable if one considers that 46% of the described patients had a neurological diagnosis at original admission.…”
Section: But If There's Nothing You Can Saymentioning
confidence: 99%